Au miroir de la pseudo-traduction. Ironisation du traduire et traduction de l’ironie - Martens, David (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Pseudo-translations of literature often produce rich encounters between translation and irony. By faking the formal features and conventions of translation, these texts are ludic means of calling into question, in a parodic mode, certain characteristics of the very type of literature to which they pretend to belong. In so doing, they expose idealized representations of those genre and the practice of translation. This study, based on pseudo¬translations by Mérimée and Queneau, examines not only the translation of word-play involving several languages but also those parts of the text which mock the very possibility of translation. This produces situations in which pseudo-translators and real translators alike find themselves forced to forego translating, in its strictest sense, certain passages in order to preserve the ironic play of the original.